Mapeamento da proteção das marcas do setor bancário no Brasil - Santos, Rosa Elaine Andrade (2016)
The brands were product identification tools and services from the fourteenth century the craft guilds. Since then, there is a greater connection of enterprises of various branches of production, the creation and protection of your brand. The Brazilian banking sector as one of the world's best, invests starkly in their corporate brand. The legal relation, brand protection is through Law 9.279 / 1996, known as the Industrial Property Law, which regulates about what can be protected as a trademark. The National Institute of Industrial Property - INPI, the body that analyzes the distinctiveness, originality and visual identity of this asset, grants the ownership of the trademark. Allocated as intangible assets has been increasing in recent years in the largest Brazilian banks. Some already appear as banks with strong brands in the current economic scenario. Thus increasing the value of their shares, directly influencing the results of these corporations. And in relations with their customers and target audience in order to keep them faithful, the banking sector is constantly investing in changes in the layout for purposes of access facilities to banks and new products, and the visual attraction is the best mechanism for that. Thus, the highlight of the value of certain benchmark creates customer satisfaction environment and greater liquidity in the financial market. The objectives of this study are to analyze the financial return of banks to protect their brands, the impact of this protection in the market competitiveness, describe the protective structures, study of the intangible asset valuation processes and their competitive potential, as well as investigate economic indicators and performance through brand association to the bank. Data analysis will be through qualitative and quantitative research of the 20 largest Brazilian banks and strong brand history in the market. Since this sample corresponds to more than 90 % of the banking market operating in the country.